2019
DOI: 10.1111/cdoe.12513
|View full text |Cite
|
Sign up to set email alerts
|

Poor diet predicts periodontal disease development in 11‐year follow‐up study

Abstract: Objective To study whether diets based on the Nordic food culture and dietary recommendations are related to periodontal disease development. Methods The data were based on the Health 2000 and 2011 Surveys (BRIF8901). The participants were aged 30‐49 in 2000, periodontally healthy, without diabetes or rheumatoid arthritis. Analyses were made in the total study population (n = 240) and among nonsmokers (n = 193) in 2011. Periodontal condition was determined in a clinical examination, and the number of teeth wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
1
21
1
Order By: Relevance
“…The importance of the frequency of sugar consumption over the amount was shown in some studies [18,43]. In an 11-year follow-up study, poor diet predicted periodontal disease development [44]. Our findings demonstrated the associations between frequency of confectionary consumption and oral health in women.…”
Section: Discussionsupporting
confidence: 67%
“…The importance of the frequency of sugar consumption over the amount was shown in some studies [18,43]. In an 11-year follow-up study, poor diet predicted periodontal disease development [44]. Our findings demonstrated the associations between frequency of confectionary consumption and oral health in women.…”
Section: Discussionsupporting
confidence: 67%
“…However, a significant relationship between Western (high fat, low fiber, processed carbohydrate) or prudent (whole grains, fruits, vegetables) diets with periodontal disease incidence was not observed, but periodontitis did significantly increase with Western diet consumption among obese individuals, specifically. An 11-year follow-up study performed by Jauhiainen et al (2020) found that, among 240 individuals, poor diets [as determined by the Baltic Sea Diet (BSD) and Recommended Finnish Diet Scores (RFD)], were associated with the development of deepened periodontal pockets among middle-aged adults. Healthy diets among the RFD and BFD included fruits, vegetables, a higher white meat and fish consumption, fibrous cereal grains (rye, oats, barley), and those with a higher ratio of unsaturated fatty acids to saturated fatty acids.…”
Section: In With the New: Additional Players In Periodontal Disease Etiology Food For Thought: The Role Of Diet In Periodontal Diseasementioning
confidence: 99%
“…The method involves the grouping of nutrients, foods, or food groups that are commonly consumed together. A number of studies have used dietary pattern analysis to examine the relationship between diet and periodontal disease (Al-Zahrani et al, 2005;Bawadi et al, 2011;Jauhiainen et al, 2016Jauhiainen et al, , 2020Salazar et al, 2018;Wright et al, 2020;Alhassani et al, 2021;Li et al, 2021). Most of these studies have used a "priori" approach, which evaluates dietary intake using pre-defined scoring classifications based on dietary guidelines or knowledge of diet and disease relationships.…”
Section: Introductionmentioning
confidence: 99%